IDEOLOGI DALAM STRUKTUR TEMA-REMA DAN TRANSITIVITAS LAGU CAMPURSARI SESIDHEMAN - Kristiandi Kristiandi; Teguh Sarosa; Sumarlam Sumarlam (PRASASTI: Journal of Linguistics, 2020)
This aticle reveals the ideology proposed in the campursari song entitled Sesideman written by Ki Dalang H Sukron Suwondo. This Critical Discource Analisys (CDA) is based on Halliday’s Systemic Functional Linguictics (SFL) as its analytical framework and Fairclough’s Dialectical Relational model as the conceptual framework. Conceptually, the analysis of the song refers to the three dimensions of CDA proposed by Fairclough. The Theme-Rheme and transitivity systems are used to describe the micro structure of the text, interpret the text, and explain the relations between interations contained in the lyric of the song as refected in the text with the social practices associated with the lyric of the song. The Theme-Rheme structure of the song Sesideman lyric consists of macro theme of the Bowo, the intro part of the lyric, and hyper-theme in the main lyric. The mscro theme structure and the transitivity of the Bowo part depict the background, process, and the effect of the actions committed by the characters in the story contained in the lyric. The hyper-theme structure and the transitivity of the main part of the lyric depict the decision making, the cuases of decision making, and the consequence resulted in the decision making, which includes the material and non-material values. The transitivity of the song lyric is dominated by material process depicting the action committed by the male and female characters of the song lyric. As a form of of social practice and a means to shape society, the campurari song Sesideman depicts the ideology proposed by the song writer upon the phenomena happening in the community surrounding shadow puppet artits (traditional Javanese song singers and pupeteers).